Functions of ventral visual cortex after bilateral medial temporal lobe damage. (August 2020) - Kim, Jiye G.; Gregory, Emma; Landau, Barbara; McCloskey, Michael; Turk-Browne, Nicholas B.; Kastner, Sabine
Abstract: Repeated stimuli elicit attenuated responses in visual cortex relative to novel stimuli. This adaptation can be considered as a form of rapid learning and a signature of perceptual memory. Adaptation occurs not only when a stimulus is repeated immediately, but also when there is a lag in terms of time and other intervening stimuli before the repetition. But how does the visual system keep track of which stimuli are repeated, especially after long delays and many intervening stimuli? We hypothesized that the hippocampus and medial temporal lobe (MTL) support long-lag adaptation, given that this memory system can learn from single experiences, maintain information over delays, and send feedback to visual cortex. We tested this hypothesis with fMRI in an amnesic patient, LSJ, who has encephalitic damage to the MTL resulting in extensive bilateral lesions including complete hippocampal loss. We measured adaptation at varying time lags between repetitions in functionally localized visual areas that were intact in LSJ. We observed that these areas track information over a few minutes even when the hippocampus and extended parts of the MTL are unavailable. LSJ and controls were identical when attention was directed away from the repeating stimuli: adaptation occurred for lags up to three minutes, but not six minutes. However, when attention was directed toward stimuli, controls now showed an adaptation effect at six minutes but LSJ did not. These findings suggest that visual cortex can support one-shot perceptual memories lasting for several minutes but that the hippocampus and surrounding MTL structures are necessary for adaptation in visual cortex after longer delays when stimuli are task-relevant.